Blood Pressure Changes on Tooth Extraction Using Local Anesthesia Contains 1:80,000 Epinephrine at Jatinangor Primary Health Care - Muhammad A Wijaya; Marlianti Hidayat; Trully D Sitorus (Journal of Medicine and Health, 2018)
Hypertension is a systemic disorder which included as one of the disease with highest prevalence in the world, particularly in Indonesia. One problem that is commonly faced by hypertension patients is administration of local anesthetic containing epinephrine 1:80.000 that needs to be given before undergoing tooth extraction procedure in primary health care setting. Administration of anesthetics is risky because it can cause sudden blood pressure increase that may cause complications. This study aims to observe the increased of blood pressure after being given local anesthetic containing epinephrine 1:80.000. This is a descriptive quantitative study conducted in April-August 2017 in Puskesmas Jatinangor. Blood pressure data is primary data, acquired from normotension and prehypertension patients aged 18-50 year who undergoes tooth extraction procedure. Blood pressure were measured before and after given local anesthetic. Result showed that there were increase in mean systolic blood pressure as much as 3.43 mmHg. Increase in systolic blood pressure occurs from the effect of epinephrine that causes constriction of the blood vessels. It is concluded that administration of local anesthetic containing epinephrine 1:80.000 before tooth extraction procedure is relatively safe and can be considered to be used in pre-hypertension patients, but not in higher hypertension stages.